Wielowymiarowe aspekty ubóstwa - statystyczna analiza zasobów dóbr trwałego użytku w gospodarstwach domowych rolników - Dudek, Hanna (Multidimensional Aspects of Poverty - Statistical Analysis of Durable Goods in Farmers' Households, 2008)
Multidimensional aspects of poverty based on the concept of order of acquisition of durable goods is undertaken in this paper. The idea is that in general households acquire durable goods in a given order which reveals information on their wealth. In order to derive the impact of various explanatory variables on the degree of deprivation of the farmers' households ordered logit models were applied. The empirical analyses were based on the Household Budget Survey carried out by the Central Statistical Office in 2003.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 511-518